Physicochemical and preliminary phytochemical analysis of different brands ofHingwashtak churna; a polyherbal medicine in Sri Lanka - Dassanayaka, G.G.; Sivasinthujah, S.; Christy Jeyaseelan, T. (Ayurveda Sahiti Prabha, 2024)
Hingwashtak churna is a polyherbal medicine, used to treat gastrointestinal diseases like gastric ulcers, bloating, acidity, and joint disease. The quality evaluation of hingwashtak churna is needed for its acceptability and safety for stakeholders. Therefore, this study focused on the evaluation of physiochemical and preliminary phytochemicals of different selected marketed brands of polyherbal medicine “hingwashtak churna” in Kurunegala, Sri Lanka. Three brands of powder form (H1, H2 & H3) of Hingwashtak churna samples were purchased in Kurunegala, Sri Lanka. Preliminary phytochemical screening and physio-chemical tests were carried out for each brand. The results were analyzed with one-way ANOVAs using SPSS 22. The results of physico-chemical parameters obtained from the study showed that there was a significant difference (Ρ > 0.05) among all three marketed brands as well as between each and other brands. Phytochemical screening of aqueous extract revealed the presence of carbohydrates, reducing sugar, flavonoids, saponins, tannins, steroids, phenols and ascorbic acid in all the brands. There was a significant difference in the flow properties of the powders from all three brands. Most of the parameters of the physiochemical tested brands of Hingwashtak Churna had roughly similar values to previous studies. As no published data are available in Sri Lanka, this preliminary profile could be a reference in future studies. However, further analysis has to be done in order to standardize the product according to the WHO guideline on Quality control methods for medicinal plant materials. 1082* Corresponding Author: Sivasinthujah SrikokulanDepartment of Pharmacy, Faculty of Allied Health Sciences, University of Jaffna. Sri Lanka. Email Id:ssinthujah@univ.jfn.ac.lk
Keywords: Polyherbal medicine; Hingwashtak churna; Sri Lanka; Phytochemical; Physio-chemical